2021
DOI: 10.3390/su13179555
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Local Review Framework to Monitor and Evaluate the Progress towards Achieving Sustainable Development Goals at a City Level: Buraidah City, KSA and SDG11 as A Case Study

Abstract: Around the world, cities are on the front lines of sustainable development. They are responsible for more than 70% of global carbon emissions. Many of these cities are experiencing dangerous levels of pollution, underemployment, and health disparities. Since 2015, 193 countries have endorsed the 17 Sustainable Development Goals (SDGs), intended to help address a wide range of challenges affecting cities and ultimately secure the resources for their next generations. All states are expected to present the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…also postulated that the sustainable development of human settlements can further improve the ecological well-being of residents [29]. With respect to research methods, Osman (2021) developed the Voluntary Local Review framework to evaluate and monitor the progress of urban human settlements in Saudi Arabia to achieve SDGs [30]. Gonçalves (2020) believed that the Casa Azul Label and SBTool Urban Dahiya can be suitable for assessing the sustainability potential of human settlements in small towns of developing countries [31].…”
Section: Introductionmentioning
confidence: 99%
“…also postulated that the sustainable development of human settlements can further improve the ecological well-being of residents [29]. With respect to research methods, Osman (2021) developed the Voluntary Local Review framework to evaluate and monitor the progress of urban human settlements in Saudi Arabia to achieve SDGs [30]. Gonçalves (2020) believed that the Casa Azul Label and SBTool Urban Dahiya can be suitable for assessing the sustainability potential of human settlements in small towns of developing countries [31].…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not the practice is environmentally sustainable, it is likely to move on if the economic analysis shows that it is advantageous from the viewpoint of a land user [43]. Economic analysis should also take into account the destruction of land resources and the subsequent decline in productivity [44]. This research emphasizes the need for strong governance institutions for a global approach to land management.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive analysis of economic, environmental, and social factors is required to identify various degrees of urbanization that are sustainable [37,41,42]. In order to categorize the research on indicators of sustainable urbanization, most studies show that indicators should include economic development, the standard of basic public services, environmental development, and urban-rural heterogeneity [26,43,44]. Kotsoni et al (2017) evaluated urbanization based on different perspectives on city size and nature of existing infrastructure, public welfare, and integration of urban and rural areas, as well as the existing economic structure [29].…”
Section: Indicators Of Urbanization Qualitymentioning
confidence: 99%
“…SDG 11 identifies the need to "make cities and human settlements inclusive, safe, resilient and sustainable" [18]. It suggests that increasing inclusion, safety, resilience, and sustainability will pave the way for the other SDGs that seek to end poverty, increase equality, boost economic growth, and ensure that residents are living healthy lives [56,57]. SDG 11 identifies resilience as the driving force behind sustainable development, with the urban system needing to maintain consistency throughout all acute shocks, serious stresses, and environmental challenges, to achieve sustainability in a healthy and resilient city.…”
Section: The Sdgs For Creating Sustainable Citiesmentioning
confidence: 99%
“…The study identified 16 indicators that could be utilized to measure progress toward sustainable development in cities. They are derived from the literature on the SDGs in the context of cities [56,59,60,95,[101][102][103][104], as well as the literature on healthy and pandemic-resilient cities [59,78,102] and on sustainability [37,48,[105][106][107][108].…”
mentioning
confidence: 99%